PENGARUH PERTUMBUHAN EARNING PER SHARE, DIVIDEN PER SHARE, RETURN ON INVESTMENT DAN RETURN ON EQUITY TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI LQ 45 - Amir Hidayatulloh; Beni Suhendra Winarso (Universitas Ahmad Dahlan, 2013)
The objective of this research is to find out the effect of the growth of earning per share, deviden per share, return on investment and return on equity of stock return on registered companies in the LQ 45. The populations of this research are companies in Indonesian Stock Exchange. The sampling technique in this research uses by purposive sampling with the available data in 2005 – 2006, registered in the LQ-45 period 2006 – 2010 respectively, announced a profit and distributing dividends in a row, so that the sample used amounted to 15 companies. The statistical method used is multiple regresion to test a classical assumtion first. T statistical test show that the growth of Earning Per Share effect on stock return H+3, growth Dividend Per Share effect on stock return in the H-5 and H+4, growth of Return On Investment effect on stock return in return H+1, whereas Return On Equity effect on stock return H+3